2015
DOI: 10.1177/2055116915608202
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic neutrophilic leukocytosis syndrome in a cat with recurrent mammary carcinoma

Abstract: Case summaryA spayed 12-year-old female domestic shorthair cat presented with nodular lesions on the ventral-right thoracic wall after complete mastectomy 4 months previously. The prior diagnosis was tubulopapillary mammary carcinoma with axillary lymph node metastasis, and a recurrence was confirmed. A gradual and sequential increase in the total number of leukocytes with severe neutrophilia (95.632/µl) developed over the course of the illness, along with an increase in the size of the recurrent mass. The sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Studies in humans have shown that carcinoma-associated thrombocytosis may be related to the tumor production of granulocytemacrophage colony stimulating factors (GM-CSF) and IL-6 [3,36]. Our research group previously reported a paraneoplastic leukocytosis in a cat with mammary gland carcinoma expressing GM-CSF [12].…”
Section: Discussionmentioning
confidence: 93%
“…Studies in humans have shown that carcinoma-associated thrombocytosis may be related to the tumor production of granulocytemacrophage colony stimulating factors (GM-CSF) and IL-6 [3,36]. Our research group previously reported a paraneoplastic leukocytosis in a cat with mammary gland carcinoma expressing GM-CSF [12].…”
Section: Discussionmentioning
confidence: 93%
“…Paraneoplastic leukocytosis is a severe neutrophilia accompanied by a left shift (often termed a leukemoid response) caused by tumor cell secretion of a substance that stimulates bone marrow maturation and release of white blood cells. 9 In the dog and cat, tumors causing an established (defined as secretion of a functional peptide or hormone + resolution of the leukocytosis following tumor removal) or probable (defined as resolution of the leukocytosis following tumor removal) paraneoplastic leukocytosis include pulmonary carcinoma (papillary, adenocarcinoma, squamous cell), [10][11][12] rectal polyp, 13,14 renal carcinoma (tubular, transitional cell), [15][16][17][18] mammary carcinoma, 19 and dermal tubular adenocarcinoma. 12 release from the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence, regional malignancy, local invasion and paraneoplastic syndromes are known consequences associated with numerous types of neoplasia. [17][18][19][20][30][31][32] Applying knowledge from literature published from their native environments while including their current environmental risk factors, such as age and sunlight exposure, are all important aspects of a camel's veterinary exam. Performing a complete physical exam, gait evaluation, diagnostic bloodwork and taking deep biopsy samples can help diagnose neoplasia like SCC early, increasing treatment options and potentially improving prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential causes of the bone marrow erythroid hypoplasia include chronic infection or inflammation as seen in this case (though unlikely as the fibrinogen was within normal limits). 29 There is also the possibility it had a paraneoplastic neutrophilic leukocytosis  of  developing, which has been described in dogs 30 and cats 31 because the patient's white blood cell count, specifically neutrophils, increased fourfold before to after operation in the face of antimicrobial therapy. Another potential cause of the neutrophilic leukocytosis includes an increase after operation from a surgical site infection, which would cause local inflammation to the area of the wound, or a mild aspiration pneumonia from postoperative regurgitation, following extubation of the endotracheal tube after surgery.…”
Section: Discussionmentioning
confidence: 99%